Chapter Predicting language-learning difficulty - Cysouw, Michael (De Gruyter, 2013)
The difficulty people have in learning a foreign language strongly depends on how different this language is from their native tongue (Kellerman 1979). Although this statement seems uncontroversial in the general form as it is formulated here, the devil lies in the detail, namely in the problem how to define differences between languages. In this paper, I investigate various factors that quantify differences between languages, and explore to which extend these factors predict language learning difficulty. This investigation results in concrete predictive formulas that derive the learning difficulty for native English speakers depending on a small selection of linguistic factors of the language to be learned.